Modelling Hydrodynamic and Sedimentation Processes in Large Lowland Rivers: An Application to the Paraná River (Argentina) - Garcia, Marina (2013)
In the last decade 1D, 2D and 3D numerical models have been extensively used to simulate river-floodplain hydraulics and sediment deposition processes in floodplains. Large river-floodplain ecosystems in lowland areas show characteristic reach lengths of the order of hundred of kilometers, floodplain widths of the order of tens of kilometers and river widths of the order of a few kilometers. The floodplain itself shows also a very complex geomorphology. Computationally intensive water flow and sediment transport models cannot take into account these peculiarities, and particularly the large time and space scales involved. On one hand, 1D models are not appropriated because the one-dimensional flow description is not representative of the complex flow pattern; on the other hand, higher dimensionality models, even if they can provide the necessary level of processes representation at small spatial scales, cannot be applied over large time and space scales due to the computational demands. An alternative to high resolution models is the implementation of quasi-2D models which can capture the fundamental characteristic of water flow and sediment dynamics in those situations. Thus, a compromise between computational costs and processes representation can be achieved. In this work a quasi-2D model, suitable for the time-dependent water and sediment transport processes simulation in large lowland river systems, including their floodplain, is presented. Water flow and sediment equations are represented by means of the interconnected irregular cells scheme. Different simplifications of 1D Saint Venant equations are used to represent the discharge laws between fluvial cells. Spatially-distributed transport and deposition of fine sediments throughout the river-floodplain system are simulated. The model is applied over a 208 km reach of the Paraná River between the cities of Diamante and Ramallo (Argentina) and involving a river-floodplain area of 8100 km². After calibration and validation, the model is applied to predict water and sediment dynamics during synthetically generated extraordinary floods of 100, 1000 and 10000 years return period. The potential impact of a 56 km long road embankment constructed across the entire floodplain was simulated. Results with and without the road embankment shows that upstream water levels, inundation extent, flow duration and sediment deposition increases in the presence of the embankment.